The National Longitudinal Study of Adolescent Health (Add Health) Sibling Pairs Data - Harris, Kathleen Mullan (2012)
This article describes the design and phenotype and genotype data available for sibling pairs with varying genetic relatedness in the National Longitudinal Study of Adolescent Health (Add Health). Add Health is a nationally-representative longitudinal study of over 20,000 adolescents in the U.S. in 1994-95 who have been followed for fifteen years into adulthood. The Add Health design included oversamples of more than 3,000 pairs of individuals with varying genetic resemblance, ranging from monozygotic twins, dizygotic twins, full siblings, half siblings, and unrelated siblings who were raised in the same household. Add Health sibling pairs are therefore nationally representative and followed longitudinally from early adolescence into adulthood with 4 in-home interviews during the period 1994-2009. Add Health has collected rich longitudinal social, behavioral, environmental, and biological data, as well as buccal cell DNA from all sample members, including siblings pairs. Add Health has an enlightened dissemination policy and to date has released phenotype and genotype data to more than 10,000 researchers in the scientific community.